The genomic landscape of language: Insights into evolution. Issue 1 (8th December 2017) - Mountford, Hayley S; Newbury, Dianne F
Abstract: Studies of severe, monogenic forms of language disorders have revealed important insights into the mechanisms that underpin language development and evolution. It is clear that monogenic mutations in genes such as FOXP2 and CNTNAP2 only account for a small proportion of language disorders seen in children, and the genetic basis of language in modern humans is highly complex and poorly understood. In this review, we examine why we understand so little of the genetic landscape of language disorders, and how the genetic background of an individual greatly affects the way in which a genetic change is expressed. We discuss how the underlying genetics of language disorders has informed our understanding of language evolution, and how recent advances may obtain a clearer picture of language capacity in ancient hominins.